Insidensi Infectious Hypodermal And Hematopoietic Necrosis Virus (IHHNV) Dan Infectious Myonecrosis Virus (IMNV) Pada Udang Putih (Litopenaeus Vannamei) Di Pertambakan Sekitar Teluk Lampung Tahun 2010 Dengan Metode Analisis Polymerase Chain Reaction (PCR) - Endang Dwi Kusumaningrum; Wardiyanto -; Toha Tusihadi (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
The purpose of this experiment was to determine the IMNV incidence rate in white shrimp at ponds in Lampung Bay in 2010 and known the pattern of incidence rate from 2007 to 2010. The experiment was conducted on October through December 2010 in ​​culture ponds in the Bay of Lampung and sample examination carried out in Main Center of Mariculture Development of Lampung. The research method was conducted includes, examination of samples by polymerase chain reaction technique and secondary data collection through interviews and data collection, followed by descriptive analysis of data. Prevalence assumption used in this study was 10%. The results showed that there was 7 locations were positive IMNV from 12 locations examination in white shrimp ponds in 2010. The value of incidence was 7.14%, 100%, and 58.33% in 2008, 2009, and 2010, respectively.